Ocular direct current stimulation affects retinal ganglion cells - Maren-Christina Blum (Nature Portfolio, 2021)
Abstract Ocular current stimulation (oCS) with weak current intensities (a few mA) has shown positive effects on retinal nerve cells, which indicates that neurodegenerative ocular diseases could be treated with current stimulation of the eye. During oCS, a significant polarity-independent reduction in the characteristic P50 amplitude of a pattern-reversal electroretinogram was found, while no current stimulation effect was found for a full field electroretinogram (ffERG). The ffERG data indicated a trend for a polarity-dependent influence during oCS on the photopic negative response (PhNR) wave, which represents the sum activity of the retinal ganglion cells. Therefore, an ffERG with adjusted parameters for the standardized measurement of the PhNR wave was combined with simultaneous oCS to study the potential effects of direct oCS on cumulative ganglion cell activity. Compared with that measured before oCS, the PhNR amplitude in the cathodal group increased significantly during current stimulation, while in the anodal and sham groups, no effect was visible (α = 0.05, pcathodal = 0.006*). Furthermore, repeated-measures ANOVA revealed a significant difference in PhNR amplitude between the anodal and cathodal groups as well as between the cathodal and sham groups (p* ≤ 0.0167, pcathodal − anodal = 0.002*, pcathodal − sham = 0.011*).